PENGARUH KUALITAS PRODUK, HARGA DAN ULASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEE (Studi Kasus Pada Brand Manly Cloth di Kota Sukoharjo) - Fajar Tri Wibowo; Sri Wijiastuti (Universitas Bina Taruna Gorontalo, 2022)
This study aims to determine the effect of product quality, price and product reviews on purchasing decisions at Shopee (a case study on the Manly Cloth brand in the city of Sukoharjo). The use of the method to determine the sample is in the form of a non-probability sampling technique with a purpose sampling method so that a number of 100 respondents are obtained. Respondent data was obtained by distributing questionnaires that had been compiled to respondents through online media. From a population of 100 people, using probability sampling technique. The number of samples obtained is 100 people. The analysis used is multiple linear regression using SPSS Version 26. Based on the results of the analysis, it is known that the influence of product quality, price and product reviews has a positive and significant effect on purchasing decisions at Shopee on the Manly Cloth brand in Sukoharjo.